Improvement of parboiled brown rice properties using pre-germination process - Yamirudeng, Ku Rosiyah; Pinkaew, Panyapathk; Detchewa, Pakkawat; Naivikul, Onanong (Agriculture and Natural Resources, 2022)
Importance of the work: Germination and parboiling were employed to improve the parboiled pre-germinated brown rice production. Objectives: To improve parboiled brown rice properties using a pre-germination process. Materials & Methods: Pre-germinated brown rice (PGBR) samples were prepared from paddy of Thai rice cultivars: Chai Nat1 (CNT1), Riceberry (RB) and Sun-Pah-Twang1 (SPT1). All samples were soaked in water at 30 °C for 12 hr and then incubated at 30 °C for 32–38 hr. Subsequently, all PGBR samples were parboiled under mild (100 °C, 10 min, 0 bar) and severe conditions (120 °C, 10 min, 1.05 bar) for comparison, before being dried until the moisture content was less than 12%. Later, all samples were analyzed for their physical, chemical and physicochemical properties. Results: Increased head rice yield and decreased yellowness were significantly affected by severe parboiling, while mild parboiling increased the redness of PPGBR from CNT1and SPT1. Both conditions of parboiling increased the crude protein (9.27–10.70%) and lipid (3.69–4.64%) contents but decreased the total starch content (80.78–81.98%). The alkali spreading score of CNT1 was 5 points (gelatinization temperature (GT) at 70–74 °C), while both RB and SPT1 had scores of 6 points (GT at 65–69 °C) under mild and severe parboiling, respectively. All three Thai rice cultivars showed a V-type X-ray diffraction pattern. Scanning electron micrographs confirmed gelatinization of the PPGBR for all three Thai rice cultivars with parboiling. Texture analysis revealed that cooked PPGBR had a lower hardness than cooked PBR for all three Thai rice cultivars. Main finding: Combined severe parboiling with germination improved the PPGBR quality of all rice cultivars.